CONCEPCIONES DE APRENDIZAJE QUE ORIENTAN LA CONSTRUCCIÓN DE LOS PLANES DE ESTUDIO DE LA CARRERA DE PSICOPEDAGOGÍA DE LA UFLO Y DE LA UNCO - S, Mainou (European Scientific Journal, ESJ, 2015)
The basic aim of this paper was to identify and analyze the conceptions of learning in students studying Educational Psychology at the National University of Comahue and the University of Flores at Comahue. This study was carried out at different times during their undergraduate training under the respective curricula. It employs the ideas developed before and during college, which guides the construction of various conceptions of learning.